Competence of information technology awareness of convergent editorial journalists (in the case of Uzbekistan editorials) - Sokhiba MULLAEVA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
as a result of digitalization, the format of journalistic activity has also changed radically. This requires journalists to be competent in information technology awareness. The article examines the extent to which employees of convergent editorial offices in Uzbekistan know and can use information technologies in creating content based on the results of a survey.